Sejarah Perdagangan Babi dari Pulau Bulan Batam ke Singapura, 1987-2023 - Arman, Dedi (Mahesa Research Center (PT. Mahesa Global Publishing), 2023)
This research delves into the pig trade history from Pulau Bulan, Batam, to Singapore spanning 1987 to 2023. In response to the 1984 policy eliminating domestic livestock farming, Singapore became reliant on imported meat. Employing a historical research method and drawing on literature reviews, the study identifies PT Indo Tirta Suaka's Pulau Bulan pig farm as Southeast Asia's largest and Singapore's primary live pig importer, initiating exports in 1987. Disruptions occurred, such as Singapore's cessation of pig supplies from Malaysia during Foot and Mouth Disease (FMD) outbreaks in Sarawak (1999-2017) and the Covid-19 pandemic. However, a significant setback unfolded with the detection of African Swine Fever (ASF) on April 19, 2023. Subsequent tests confirmed ASF in Pulau Bulan pig samples, prompting Singapore to officially halt pig supplies. This resulted in a substantial monthly and yearly loss of approximately IDR 3.5 billion and IDR 1.1 trillion, respectively, in pig exports from Pulau Bulan to Singapore.